Nonbiopsy Diagnosis of Cardiac Transthyretin Amyloidosis - Gillmore, Julian D.; Maurer, Mathew S.; Falk, Rodney H.; Merlini, Giampaolo; Damy, Thibaud; Dispenzieri, Angela; Wechalekar, Ashutosh D.; Berk, John L.; Quarta, Candida C.; Grogan, Martha; Lachmann, Helen J.; Bokhari, Sabahat; et al. (Circulation (New York, N.Y.), 2016)
BACKGROUND—Cardiac transthyretin (ATTR) amyloidosis is a progressive and fatal cardiomyopathy for which several promising therapies are in development. The diagnosis is frequently delayed or missed because of the limited specificity of echocardiography and the traditional requirement for histological confirmation. It has long been recognized that technetium-labeled bone scintigraphy tracers can localize to myocardial amyloid deposits, and use of this imaging modality for the diagnosis of cardiac ATTR amyloidosis has lately been revisited. We conducted a multicenter study to ascertain the diagnostic value of bone scintigraphy in this disease. METHODS AND RESULTS—Results of bone scintigraphy and biochemical investigations were analyzed from 1217 patients with suspected cardiac amyloidosis referred for evaluation in specialist centers. Of 857 patients with histologically proven amyloid (374 with endomyocardial biopsies) and 360 patients subsequently confirmed to have nonamyloid cardiomyopathies, myocardial radiotracer uptake on bone scintigraphy was >99% sensitive and 86% specific for cardiac ATTR amyloid, with false positives almost exclusively from uptake in patients with cardiac AL amyloidosis. Importantly, the combined findings of grade 2 or 3 myocardial radiotracer uptake on bone scintigraphy and the absence of a monoclonal protein in serum or urine had a specificity and positive predictive value for cardiac ATTR amyloidosis of 100% (positive predictive value confidence interval, 98.0–100). CONCLUSIONS—Bone scintigraphy enables the diagnosis of cardiac ATTR amyloidosis to be made reliably without the need for histology in patients who do not have a monoclonal gammopathy. We propose noninvasive diagnostic criteria for cardiac ATTR amyloidosis that are applicable to the majority of patients with this disease.